A model of integrated regional logistics hub in supply chain. Issue 10 (26th November 2018) - Lu, Hua; Li, Ling; Zhao, Xueyu; Cook, David
ABSTRACT: A regional logistics hub is a constellation of multiple logistics facilities in a region of several provinces or states. This research models an integrated regional logistics hub with consideration of time-phased demand in a multi-echelon, multi-period, and capacitated logistics network. The integrated logistics hub considers three phases based on the characteristics of China's five-year planning policy. By applying mixed integer linear programming, the greedy heuristics approach, the particle swarm optimization algorithm, and the Hungarian method, the location of logistics facilities at different echelons of a supply chain is identified and the needs for facility expansion or closing during different time periods are determined.